Instructional Counselling: The Counsellor as Teacher - Hiebert, Bryan A.; Martin, Jack; Marx, Ronald W. (Canadian Journal of Counselling and Psychotherapy, 2012)
Counselling is an instructional activity wherein clients act as learners and counsellors act as teachers. It is argued that an adoption of this viewpoint has profound and far-reaching implications for counselling practice, counselling effectiveness research, and counsellor training. Such implications are discussed, and an instructional counselling model for counsellor training is briefly described.